Writing history in the global era - Hunt, Lynn 1945- (Norton, 2014)
"With history in ferment, leading historian Lynn Hunt rethinks why history matters and how it should be written. George Orwell wrote that 'history is written by the winners.' Even if that seems a bit too cut-and-dried, we can say that history is always written from a viewpoint but that viewpoints change, sometimes radically. The history of workers, women, and minorities challenged the once-unquestioned dominance of the tales of great leaders and military victories. Then cultural studies...including feminism and queer studies...brought fresh perspectives, but those too have run their course. With globalization emerging as a major economic, cultural, and political force, Lynn Hunt examines whether it can reinvigorate the telling of history. In tandem, she proposes a sweeping reevaluation of individuals' agency and their place in society as the keys to understanding the way people and ideas interact. Writing History in the Global Era is bound to shake up the discipline and break new ground for historical studies"...Provided by publisher